ERRORS IN INDONESIAN-ENGLISH TRANSLATIONS BY STUDENTS OF ENGLISH EDUCATION PROGRAM - M Fajar K Lubis; Masitowarni Siregar; Indra Hartoyo (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This research was aimed to analyze errors made by students in translating Indonesian text to English using the classification made by Gentzler. The subject of this research was students who took Translation subject in 2018/2019 academic year in English Education study program in State University of Medan. The instrument of collecting data was a translation test from Indonesian to English consisting of three genres: narrative, descriptive, and analytical exposition. 30 students were divided into 3 groups of 10, each translating different genres. The errors in translations were classified into five types of errors as classified by Gentzler. The result showed that inversion, omission, addition, deviation, and modification errors were found in students’ translations. Deviation and modification errors formed 90% of all errors combined. The errors were caused by interlingual and intralingual interference. They were collocational errors, choosing inappropriate meaning when looking up the dictionary, word per word translation, and overgeneralization. Key words: Translation, Errors in Translation, English Education Study Program